Dosage compensation in the process of inactivation/reactivation during both germ cell development and early embryogenesis in mouse - Xiaoyong Li (Nature Portfolio, 2017)
Abstract Ohno proposed that dosage compensation in mammals evolved as a two-step mechanism involving X-inactivation and X-upregulation. While X-inactivation is well characterized, it remains to further analysis whether upregulation of the single activated X chromosome in mammals occurs. We obtained RNA-seq data, including single-cell RNA-seq data, from cells undergoing inactivation/reactivation in both germ cell development and early embryogenesis stages in mouse and calculated the X: A ratio from the gene expression. Our results showed that the X: A ratio is always 1, regardless of the number of X chromosomes being transcribed for expressed genes. Furthermore, the single-cell RNA-seq data across individual cells of mouse preimplantation embryos of mixed backgrounds indicated that strain-specific SNPs could be used to distinguish transcription from maternal and paternal chromosomes and further showed that when the paternal was inactivated, the average gene dosage of the active maternal X chromosome was increased to restore the balance between the X chromosome and autosomes. In conclusion, our analysis of RNA-seq data (particularly single-cell RNA-seq) from cells undergoing the process of inactivation/reactivation provides direct evidence that the average gene dosage of the single active X chromosome is upregulated to achieve a similar level to that of two active X chromosomes and autosomes present in two copies.